DIGITAL TRANSFORMATION AND ENTREPRENEURSHIP IN TURKEY (Third Sector Social Economic Review, 2022)
With the rapid and global developments in information and communication technologies, digital transformation has gained momentum and the importance of entrepreneurship has increased in terms of national economies. Experienced technological developments have led to significant changes in public and institutional areas, especially in entrepreneurship. Especially with the pandemic process, the digital transformation process in many fields, especially in entrepreneurship, has accelerated and consumer needs have been met through digital platforms. This situation revealed the necessity of digital transformation and made significant contributions to the development and diversification of digital marketing tools in terms of businesses. The purpose of this study, in case of any new entrepreneurial activity or for the digitalization of existing enterprises, with a focus on digital transformation, what should be done about the evolution of entrepreneurship into digital transformation, the studies in the literature will be explained. Considering the studies conducted in Turkey, it is considered that the study will contribute to the literature. A literature-oriented study was conducted by presenting suggestions for promoting digital transformation in the context of entrepreneurship in Turkey.
Keywords: Entrepreneurship; Entrepreneurship Programs; Digital Transformation